Viabilidade econômica de quatro intensidades de pastejo do capim Tanzânia na pecuária de corte1 - Barbero, Rondineli Pavezzi [UNESP]; De Freitas Barbosa, Marco Aurélio Alves; De Castro, Letícia Maria; De Azambuja Ribeiro, Edson Luis; Mizubuti, Ivone Yurika; Da Silva, Leandro Das Dores Ferreira; Bumbieris Jr., Valter Harry; De Souza Fortaleza, Ana Paula (Universidade Estadual de Londrina, 2012)
Were evaluated the economic effects of four grazing heights (20, 40, 60 and 80 cm) of Tanzânia grass for beef cattle. The total area was 12 acres divided into paddocks of one hectare, with three replications. We used three animals, males, Nelore per paddock, as more animals need additional adjustment to the height you want. The reduction in sward height allowed higher stocking rate, which, even with a reduction in individual performance, there was more beef production per area. The interest rate on capital given the property represented the largest share in the final cost of production. The participation of fixed variables showed a positive linear function of the increase in height from grazing, showing significant reduction of the production scale. A reduction in cost of production per hectare per year with increasing grazing height. No differences were found in certain economic indicators, and the four systems remunerate the capital invested.
Economic feasibility of four grazing intensities of Tanzania grass for beef cattle
Keywords: Agribusiness; IRR; NPV; Profit; Proftability